Ada, or Ardor: A Family Chronicle - Nabokov, Vladimir Vladimirovich, 1899-1977; Connors, Robert S.; Robert S. Connors Basic Program Collection (New York : McGraw-Hill Book Company, 1969)
Set in a "dreambright" America, at the turn of the century, Nabokovs last novel depicts an incestuous love affair, while presenting a complex puzzle of literary world play and metaphysical parody.
Keywords: Russian literature -- 20th century; Russian Literature; Fiction; Romance fiction; Love stories; Fiction; Romance fiction; Novels